2013
DOI: 10.1007/s00464-013-3287-7
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide outcomes of nontrauma splenectomy

Abstract: NTS has not been affected by regionalization, which is dissimilar to other solid-organ abdominal procedures. Indeed, the benefit of regionalization for splenectomy has not been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…1,5 Previous studies have established that elective splenectomy for malignant conditions has a higher complication rate than splenectomy for benign conditions. 3,5,6 Our study validates the risk factors associated with infectious complications from previous studies. 1,5 In our analysis, the adjusted risk for postoperative septic events remains similar between the group undergoing splenectomy for malignant indications and the group undergoing splenectomy for benign indications.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…1,5 Previous studies have established that elective splenectomy for malignant conditions has a higher complication rate than splenectomy for benign conditions. 3,5,6 Our study validates the risk factors associated with infectious complications from previous studies. 1,5 In our analysis, the adjusted risk for postoperative septic events remains similar between the group undergoing splenectomy for malignant indications and the group undergoing splenectomy for benign indications.…”
supporting
confidence: 86%
“…4,5 Splenectomy has also been established as a leading cause of thrombotic events in beta-thalassemia patients, owing to the role of the spleen in scavenging thrombogenic red blood cells and to increased numbers of activated platelets in splenectomized patients. 5,6 Iron overload (serum ferritin ≥800-1000 μg/L) in these patients has also been associated with high thrombosis rates, in view of the damaging effects of toxic iron species on the endothelium and vasculature, as well as to secondary development of multiorgan failure (heart, liver, and endocrine dysfunction). 5,7 Advancing age prolongs the exposure of patients to these risk factors, and higher rates of thrombosis have been reported in older beta-thalassemia patients (>35 years).…”
Section: Development Of a Thalassemia-related Thrombosis Risk Scoringmentioning
confidence: 99%
“…The Luft paper launched a substantial literature on the volume‐outcome relationship. It also prompted regionalization for certain operative procedures . Regionalization of adrenalectomies to high volume centers has been documented and was associated with reduced inpatient mortality .…”
Section: The Era Of Big Data Beginsmentioning
confidence: 99%
“…Colavita and colleagues found that regionalizing ventral hernia repair was not associated with reduced mortality, while costs actually increased . Zemlyak et al found no regionalization for non‐trauma related splenectomy so no basis can be claimed for a benefit in doing so.…”
Section: The Era Of Big Data Beginsmentioning
confidence: 99%